(3GddGYH h GdJOQjH GdYbdjs - (3TeYhf eMeO GdYQHjs; (3eMeO GSeGYjd eGLOIs ((3GdbGgQIs (3eQcR GdcJGH ddfTQs, 2001)
(3jYcS GdcJGH COGA eLehYI ef GddGYHjf Ydi GdeSJhi GdGhdeHj h GdYGdej aj GdGSJaGOI ef GdJOQjH GdYbdj ,eHjfG CgejI GdJcGed Hjf GdYbd h GdLSe aj JMbjb GdGfLGR GdQjGVj , ceG jJVef GdJYQja HGdJOQjH GdYbdj h jHQR CgejI GdhYj GdYbdj ddGYH djJecf ef JMbjb CMdGeg , ceG bOe NWhGJ GdHQfGeL GdYbdj GdhGLH EJHGYg(B.s
Keywords: (3GdJOQjH GdYbdjs; (3Yde GdfaS GdQjGVIs